Populated Places and Conspicuous Consumption: High Population Density Cues Predict Consumers’ Luxury-Linked Brand Attitudes - Otterbring, Tobias; Folwarczny, Michał; Tan, Lynn K. L. (Frontiers in Psychology, 2021)
Population density has been identified as an ecological factor with considerable behavioral implications. The present research aimed to examine whether the mere perception of more (vs. less) populated places can change consumers’ luxury-linked brand attitudes. To this end, we experimentally manipulated consumers’ perceptions of population density using pictorial exposure to high (vs. low) population density cues. The results revealed a significant interaction between manipulated population density and perceived brand luxury on brand attitudes. Specifically, exposure to high rather than low population density cues resulted in more positive (negative) attitudes toward brands deemed to be more (less) luxurious. These findings support our prediction that high population density cues can shift people’s perceptions in consumption contexts linked to luxury. Our work contributes to the growing stream of literature on population density and suggests that this (geo-) demographic factor can exert important downstream effects on consumer behavior.